ANTIBODIES AGAINST VESICULAR ESTOMATITIS VIRUS IN WHITE-LIPPED PECCARIES (TAYASSU PECARI) IN MADRE DE DIOS, PERU - Carruitero H., Susan (2013)
The aim of the study was to determine the presence of antibodies against New Jersey (NJ) and Indiana subtype 1 (IND-1) Vesicular Stomatitis Virus (VSV) in free-living white-lipped peccaries (Tayassu pecari) in three localities of Madre de Dios, Peru. The presence of antibodies against VSV by virus neutralization test was determined in 88 serum samples of adult male and females in apparent good health condition. Results showed that 53.4% (47/88) and 18.2% (16/88) of samples were positive to antibodies against serotypes IND-1 and NJ respectively, whereas 55.3 and 12.6% of the serum samples had neutralizing antibodies titers equal or greater than 1:32 against serotype IND-1 and NJ respectively. There was a no significant association between seropositivity of VSV and source of samples.